2020
DOI: 10.1111/jdi.13216
|View full text |Cite
|
Sign up to set email alerts
|

Iron metabolism and type 2 diabetes mellitus: A meta‐analysis and systematic review

Abstract: Aims/Introduction: Iron metabolism can directly or indirectly affect the occurrence and development of type 2 diabetes. This meta-analysis and systematic review aimed to analyze the association between serum iron metabolism indicators and type 2 diabetes. Materials and Methods: The databases PubMed and Embase were searched for studies on the correlations between serum iron metabolism indicators (iron, ferritin, transferrin, hepcidin and soluble transferrin receptor) and type 2 diabetes since January 2006. Rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 39 publications
1
74
0
Order By: Relevance
“…Conversely, the hypothesized protective role of Zn has not been well demonstrated in human studies. Dietary intake [ 12 ] or supplementation [ 21 ] of Zn seemed to regress the progression of new-onset DM, whereas serum Zn had no association with DM in meta-analyses [ 9 , 10 , 11 ]. Besides, total zinc intake from both diet and supplementation failed to demonstrate the protective role toward diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, the hypothesized protective role of Zn has not been well demonstrated in human studies. Dietary intake [ 12 ] or supplementation [ 21 ] of Zn seemed to regress the progression of new-onset DM, whereas serum Zn had no association with DM in meta-analyses [ 9 , 10 , 11 ]. Besides, total zinc intake from both diet and supplementation failed to demonstrate the protective role toward diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The association between Fe and DM is consistent. Elevated serum iron [ 34 ] and ferritin [ 9 ] as well as dietary Fe [ 16 ] were associated with an increased risk of DM. Additionally, excessive serum iron and ferritin were observed in the MetS group [ 15 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond BCAA content, the source of dietary protein is thought to influence metabolic risk due to multiple other factors such as difference in iron and amino acid content [ 153 , 154 ]. Observational studies have shown an association between ferritin and T2DM suggesting a role of high iron stores in diabetes development [ 155 ]. However, this underlying association may be more complex than this simple link and has been reported to require further investigation [ 156 ].…”
Section: Dietary Management Of Diabetesmentioning
confidence: 99%
“…Ultimately affecting insulin production and increasing the risk to insulin resistance. Moreover, weakening of the ability of the liver to use insulin and gluconeogenesis [8] .…”
Section: Ironmentioning
confidence: 99%